The visual psychology of European Upper Palaeolithic figurative art: using Bubbles to understand outline depictions. Issue 2 (14th March 2020) - Meyering, Lisa-Elen; Kentridge, Robert; Pettitt, Paul
ABSTRACT: How have our visual brains evolved, and exactly how did this constrain the specific way that animals were depicted in Upper Palaeolithic art? Here, we test predictions derived from visual neuroscience in this field. Using the example of open-air Upper Palaeolithic rock art of Portugal's Côa Valley, we point out the frequently recurring outline strategies that past artists utilized to depict the prey animals upon which they were dependent for survival. Their depictional tendency can be mirrored onto the most visually salient anatomical aspects of these species, a finding that results from our use of a visual psychological experimental programme, called Bubbles . We find a remarkable correspondence between the aspects of the anatomy of horses and bison that modern participants found most helpful in successfully discriminating between the two, and those same aspects that are elaborated most in Upper Palaeolithic art. This leads us to conclude that the visual system of Homo sapiens drove the way that important prey species were depicted, and hence, the form of their art.